2020
DOI: 10.1111/jocd.13905
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lichen planus and metabolic syndrome

Abstract: Objective Lichen planus (LP) is an idiopathic, chronic inflammatory disease. Chronic inflammatory diseases can cause metabolic complications. In the literature, data related to the relationship between lichen planus and metabolic syndrome (MS) are limited. We aimed to evaluate the relationship between MS and lichen planus with disease activity. Methods The patients diagnosed with lichen planus at the dermatology outpatient clinic between January 2018 and January 2020 were retrospectively analyzed. 98 lichen pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 19 publications
4
24
0
1
Order By: Relevance
“…In the literature, lichen planus has been associated with metabolic syndrome, dyslipidaemia, hypertension and diabetes mellitus. 1,14,15 MS was found in 50.9% of patients with LP in our study, and it was statistically significant. In addition, AN and acrochordon were present LP patients with a percentage of 43.5% and 57.4%.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the literature, lichen planus has been associated with metabolic syndrome, dyslipidaemia, hypertension and diabetes mellitus. 1,14,15 MS was found in 50.9% of patients with LP in our study, and it was statistically significant. In addition, AN and acrochordon were present LP patients with a percentage of 43.5% and 57.4%.…”
Section: Discussionsupporting
confidence: 63%
“…3 Again, in this context, the number of publications showing the relationship with MS in lichen planus patients has increased. 1,4 Acanthosis nigricans is a clinical finding described by asymptomatic plaques that are grayish-brown or black in color, raised from the skin, lichenified, velvety, and violase, with no sharp borders, located in intertriginous areas such as axilla, neck, and groin. 5 Hyperkeratosis and papillomatosis are prominent in histopathological examination.…”
mentioning
confidence: 99%
“…11,12 Besides, the risk of dyslipidemia and metabolic syndrome is higher in CLP patients. 13,14 Based on the above research findings, we speculate that Wnt5a may increase in circulation of patients with CLP. The present study was planned to evaluate whether Wnt5a is altered in the serum of patients with CLP.…”
Section: Introductionmentioning
confidence: 69%
“…18 In addition to skin involvement, LP can have some complications, including type I and type II diabetes, metabolic syndrome and coronary heart disease. 13,14 Higher risk of dyslipidemia has been proved to be a common complication in patients with LP. 13,19 The Wnt5a pathway plays an important role in the pathogenesis of various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OLP and MS should not be ignored. 18 The rate of malignant transformation of OLP is between 0% and 10%. A recent meta-analysis found that 1.1% of OLP lesions convert into OSCC, with a higher frequency among alcoholics, smokers, and people infected with hepatitis C. Invasive OLP appears to have the highest frequency of progression to OSCC.…”
Section: Overview Of Oral Lichen Planusmentioning
confidence: 99%